Hygromechanics of softwood cellulosic nanocomposite with intermolecular interactions at fiber-matrix interface investigated with molecular dynamics. (1st January 2022) - Zhang, Chi; Chen, Mingyang; Coasne, Benoit; Keten, Sinan; Derome, Dominique; Carmeliet, Jan
Abstract: Intermolecular interactions at the fiber-matrix interface strongly affect the hygromechanical behavior and overall mechanical performance of hydrophilic cellulosic nanocomposites. The mechanics of a model interface consisting of cellulose and galactoglucomannan, inspired by the natural material wood, is investigated by molecular simulations over the full hydration range. With the increment of moisture content, the composite swells anisotropically and non-monotonically with an initial shrinkage. The interphase, a 1–2 nm thick region of matrix strongly influenced by the fiber, shows features of enrichment and ordered structure distinct from bulk. Pulling tests reveal the interfacial shear strength as a function of moisture content. The stick-slip behavior is explained by the strong correlation between the number of hydrogen bonds and the interfacial shear stress, suggesting the force rendered by a single hydrogen bond to be ∼140 pN. These insights shed light on the mechanics of interface and interphase, a topic of less attention yet critical for understanding the mechanical performance of fiber-reinforced composites. Highlights: Interface of cellulosic fiber-reinforced nanocomposite is studied via molecular simulation. The composite swells anisotropically: minimal along fiber axis. An interphase, 1–2 nm thick, forms in the amorphous matrix next to the fibril. Hydrogen bond dominates the interface shear strength. One hydrogen bond provides a force of ∼140 pN.